2009
DOI: 10.1159/000228906
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Satisfaction with Flexible Bronchoscopy in a Hospital-Based Community Practice

Abstract: Background: There are no data about patients’ satisfaction with a first bronchoscopy in community practice. Objectives: The aim of this study was to assess the satisfaction with flexible bronchoscopy and the willingness to return for the procedure if needed in hospital-based community practice. Methods: Prospective administration of a questionnaire before and after flexible bronchoscopy with inclusion of 126 patients in the analysis. Results: The reliability analysis demonstrated a good internal consistency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 47 publications
2
18
2
1
Order By: Relevance
“…The discomfort experienced by patients during bronchoscopy strongly correlates to anxiety before the procedure 295 296. Adequate sedation reduces patient anxiety and improves tolerance and satisfaction with the procedure 98.…”
Section: Patient Satisfactionmentioning
confidence: 99%
“…The discomfort experienced by patients during bronchoscopy strongly correlates to anxiety before the procedure 295 296. Adequate sedation reduces patient anxiety and improves tolerance and satisfaction with the procedure 98.…”
Section: Patient Satisfactionmentioning
confidence: 99%
“…We have described a restrictive ventilatory pattern with a predominantly granulocytic acute alveolar inflammation causing significant hypoxemia [10] . The detection of PLTX remains challenging and not widely available.…”
Section: Case Reportmentioning
confidence: 99%
“…The aim of sedation is to achieve good patient tolerance, comfort and cooperation while reducing complications of the procedure [2][3][4]. Sedation is associated with high patient satisfaction and willingness to return for a repeat bronchoscopy, if necessary [5]. A survey in the UK has shown that .95% of the centres routinely perform sedated bronchoscopies [6].…”
mentioning
confidence: 99%